2017
DOI: 10.5530/jcdr.2017.4.29
|View full text |Cite
|
Sign up to set email alerts
|

Acute Impact of Balloon Mitral Valvotomy on Left Atrial Functions in Mitral Stenosis

Abstract: Background: Rheumatic mitral stenosis (MS) is associated with progressive impairment of left atrial (LA) mechanical functions. This study was conducted to assess the acute impact of Balloon Mitral Valvotomy (BMV) on these functions. Methods: This single centre observational study included 25 patients with severe MS (aged 34.1 ± 7.1 years, with mean mitral valve area of 0.74 ± 0.13 cm²), in sinus rhythm, who underwent successful BMV at our hospital. Phasic LA volumes (V max : maximal LA volume, V min : minimal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…It is also one of the most powerful predictors of new-onset AF on follow-up, progression from paroxysmal to persistent AF [ 9 , 10 ], and often precedes LA enlargement [ 11 , 12 ]. Successful percutaneous balloon mitral valvuloplasty (BMV) leads to early improvement in left atrial reservoir and conduit functions, without significantly affecting left atrial pump function [ 13 ]. We sought to evaluate the impact of successful BMV on the left atrial reservoir function and volume in patients with severe mitral stenosis using PALS.…”
Section: Introductionmentioning
confidence: 99%
“…It is also one of the most powerful predictors of new-onset AF on follow-up, progression from paroxysmal to persistent AF [ 9 , 10 ], and often precedes LA enlargement [ 11 , 12 ]. Successful percutaneous balloon mitral valvuloplasty (BMV) leads to early improvement in left atrial reservoir and conduit functions, without significantly affecting left atrial pump function [ 13 ]. We sought to evaluate the impact of successful BMV on the left atrial reservoir function and volume in patients with severe mitral stenosis using PALS.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that PTMC was not only a safe and effective surgery but also greatly improved patients' QOL, underscoring the significance of providing this procedure at an earlier stage of the disease. According to a local study done in 2019 at the Combined Military Hospital in Pakistan, the authors did not notice any post-PTMC problems such localized hematoma, mitral regurgitation, or circulatory compromise [16][17] . The patients' success rate with PTMC (mean age, 40.3 ±2.8) was very high.…”
Section: Discussionmentioning
confidence: 93%